Defining Genetic and environmental determinants of elemental homeostasis in maize (Zea mays L.): A genome-wide association study of elemental composition of maize grain - Kear, Philip James (2018)
Dissolved minerals are absorbed by plants from the soil or other sources, incorporated into seeds, leaves and other tissues that are then consumed by animals and humans, which carry those nutrients up the food chain. Plant-absorbed minerals form the source of 22 elements required by the human body for proper functionality, whether eaten directly or through meat consumption. The proportion of a plant or other organism that forms the inorganic mineral and trace elements is defined as the ionome. Study of the ionome has the potential to affect a wide range of agronomically pertinent areas affecting agriculture and society, including nutrient-use efficiency, toxicology, bio-fortification, bio-availability, bio-remediation and mitigation of toxic metals in the crops we consume. Maize is a model species, well suited to ionomic studies because of the high diversity in genic regions, but is also the most widely grown staple food crop on the planet with significant cultivation on every continent except Antarctica. Maize also provides a diverse collection of germplasm with the feasibility of creating segregating progenies and immortal genotypes through self-fertilization. This dissertation investigates the dynamic nature of field-based maize kernel concentrations of 20 elements in order to simulate ‘real-world’ situations experienced by plants grown as food, but also to reflect a plant’s necessarily complex genetic adaptation to environments. This study utilized both linkage and association mapping on multiple populations, benefiting from advantageous population design and genetic architecture. Analysis across different populations discovered significant genomic regions that co-localized with known and novel candidate genes. For all 20 elements, significant regions were most frequently found in single field locations, ranging between 219 and 7240 regions per element across locations collectively. Nevertheless, some of these regions were discovered in two or more field environments. The occurrence of significant regions ...